Pemanfaatan Tumbuhan Obat oleh Suku Togutil di Daerah Penyangga Taman Nasional Aketajawe Lolobata - APAL, ROFIDAH UMMULHARBI; ARIYANTI, NUNIK SRI; WALUJO, EKO BAROTO; DORLY, . (Departemen Biologi, Institut Pertanian Bogor, 2018)
Togutil is an indigenous tribe that lives in buffer zone of the Aketajawe Lolobata National Park (ALNP) Halmahera Island, North Maluku. This tribe still uses medicinal plants to treat diseases and health care due to limited access to the modern health care. This study aimed to identify the biodiversity and utilization of medicinal plants, as well as to analyze the index of cultural significance of the medicinal plants based on the traditional knowledge of the Togutil tribe. This research was conducted from June to November 2016. The research was conducted in 3 villages by interviewing 3 key informants and 36 respondents. The cultural significance of the medicinal plant species was analysis based on its quality, intencity, and exclusivity value. The result shows that the Togutil tribe use 69 species of medicinal plants for treating 45 categories of diseases. They are mostly used as medicine are leaves (43 species). There are several ways to use the medicinal plants, including smearing, dripping, in taking per oral and per nasal. Gluta renghas is the most important.